Metode Perhitungan Harga Pokok Produksi Tahu pada UKM Krisna Karya Mulya di Palangka Raya - Alexandro, Rinto; Uda, Tonich (Universitas Pendidikan Ganesha, 2020)
This research was conducted at Krisna Karya Mulya UKM in Panarung Palangka Raya City, the purpose of this study was to find out the method of calculating the cost of tofu production at Krisna Karya Mulya UKM in Palangka Raya. This research uses quantitative methods. The results showed that the use of the variable costing method in Krisna Karya Mulya UKM turned out to be cheaper or significant compared to using the full costing method because in the variable costing method a profit calculation was greater than the value. Meanwhile, the results of tofu production calculation in UKM Krisna Karya Mulya if using the full costing method will be greater or experience a significant increase when compared to the calculation of the variable costing method. This means that the use of variable costing methods in tofu production businesses in Krisna Karya Mulya SMEs is not appropriate because in the variable costing method the amount of overhead depreciation costs is not counted, so there are costs that should appear in the production process but become unidentified.